Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.chb.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Security and privacy in online social networking: Risk perceptions and precautionary behaviour

Abstract: A quantitative behavioural online study examined a set of hazards that correspond with security-and privacy settings of the major global online social network (Facebook). These settings concern access to a user's account and access to the user's shared information (both security) as well as regulation of the user's information-sharing and user's regulation of others' information-sharing in relation to the user (both privacy). We measured 201 non-student UK users' perceptions of risk and other risk dimensions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 52 publications
2
67
0
Order By: Relevance
“…Additionally, in the context of the social network, Internet experience has been found to predict precautionary behaviour, and further causes greater sensitivity to associated risks in using Facebook (Van Schaik et al 2018). Thus, years of experience in using the network could increase the individual's awareness of the risk associated with connecting with strangers.…”
Section: Social Network Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the context of the social network, Internet experience has been found to predict precautionary behaviour, and further causes greater sensitivity to associated risks in using Facebook (Van Schaik et al 2018). Thus, years of experience in using the network could increase the individual's awareness of the risk associated with connecting with strangers.…”
Section: Social Network Experiencementioning
confidence: 99%
“…Many studies have considered perceiving the risk associated with engaging in online activities as having a direct influence on avoiding using online services (Riek et al 2016) and more importantly as decreasing their vulnerability to online threats (Vishwanath et al 2016). Facebook users' perceived risk of privacy and security threats significantly predict their strict privacy and security settings (Van Schaik et al 2018). Thus, if online users are aware of the potential risks and their consequences that might be encountered on Facebook, they will probably avoid clicking on malicious links and communicating with strangers on the network.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…However, in the case of hacking on social media, Facebook in particular, who have experienced hacking or retrieval of personal data feel they do not get help from Facebook. Facebook should be able to warn users of personal data abuse 22 . Since not all victims of hacking know that they are being hacked and have their privacy violated.…”
Section: Internet Behavior Related To Privacy and Personal Datamentioning
confidence: 99%
“…Prior research has shown that security and privacy concerns of internet users vary across different cultural and political settings, as well as level of user expertise [59,60]. An early study of social media privacy attitudes and behavior in India used a survey of 407 participants [61].…”
Section: Global Demographic Characterizationsmentioning
confidence: 99%